Biohybrid cardiac ECM-based hydrogels improve long term cardiac function post myocardial infarction - Efraim, Yael (2017)
Injectable scaffolds for cardiac tissue regeneration are a promising therapeutic approach for progressive heart failure following myocardial infarction (MI). Their major advantage lies in their delivery modality that is considered minimally invasive due to their direct injection into the myocardium. Biomaterials comprising such scaffolds should mimic the cardiac tissue in terms of composition, structure, mechanical support, and most importantly, bioactivity. Nonetheless, natural biomaterial-based gels may suffer from limited mechanical strength, which often fail to provide the long-term support required by the heart for contraction and relaxation. Here we present newly-developed injectable scaffolds, which are based on solubilized decellularized porcine cardiac extracellular matrix (pcECM) cross-linked with genipin alone or engineered with different amounts of chitosan to better control the gel’s mechanical properties while still leveraging the ECM biological activity. We demonstrate that these new biohybrid materials are naturally remodeled by mesenchymal stem cells, while supporting high viabilities and affecting cell morphology and organization. They exhibit neither in vitro nor in vivo immunogenicity. Most importantly, their application in treating acute and long term chronic MI in rat models clearly demonstrates the significant therapeutic potential of these gels in the long-term (12 weeks post MI). The pcECM-based gels enable not only preservation, but also improvement in cardiac function eight weeks post treatment, as measured using echocardiography as well as hemodynamics. Infiltration of progenitor cells into the gels highlights the possible biological remodeling properties of the ECM-based platform.